Effect of inorganic selenium on reproductive performance of Large White Yorkshire gilts - GNANARAJ, P TENSINGH; SIVAKUMAR, T; ARUNACHALAM, S; SUNDARAM, S MEENAKSHI; RAMESH, V (The Indian Journal of Animal Reproduction, 2023)
A study was carried out to find out the influence of dietary selenium on the reproductive performance of gilts atSwine Breeding Unit, Livestock Research Station. Tamil Nadu. Twenty four Large White Yorkshire gilts, at breeding age, wererandomly allotted to three groups of eight gilts each. The dietary treatments groups were 0.1 ppm of Se. 0.3 ppm of Se andcontrol diet devoid of Se. Dietary supplementation of selenium at 0.1 ppm and 0.3 ppm resulted significantly (P
Keywords: Selenum,; reproduction; blood profile; pigs